The Study of Impact of Diversity and Inclusion on Employees Performance in ITES Industry (International Journal of Scientific Research in Science and Technology, 2024)
Diversity is the mix of people whereas inclusion is the culture in which the mix of people can come to work, feel comfortable and confident to be themselves, and work in a way that suits them and delivers your business or service needs. Inclusion will ensure that everyone feels valued and importantly, adds value. Diversity and inclusion allows organizations to be more inclusive of different ideas, cultures, and lifestyles, leading to improved company culture. In this research article the researcher focused on the factors which are significantly impact on performance of employees in ITES Industry. During the research study the researcher collected 400 data sample through the structured questionnaires and compiled by SPSS software at 0.05 significant levels. The researcher emphasized that that the attributes of diversity and inclusion at workplace such as Diverse Skill Sets, Cultural Awareness, Equal Opportunities, Inclusive Leadership, Flexible Work Policies, Training and Education have a significant impact on employee’s performance in ITES Industry. As the statistical analysis the researcher found that 91.1% respondents are in favour of attributes with respect to diversity and inclusion at workplace have a significant impact on employee’s performance whereas 4.6% does not believe in diversity and inclusion at workplace.